Wound photography for evaluation of surgical site infection and wound healing after lower limb trauma. (1st December 2021) - Bruce, Julie; Knight, Ruth; Parsons, Nick; Betteridge, Ria; Verdon, Amy; Brown, Julie; Campolier, Marta; Achten, Juul; Costa, Matt L.
Abstract : Aims: Deep surgical site infection (SSI) is common after lower limb fracture. We compared the diagnosis of deep SSI using alternative methods of data collection and examined the agreement of clinical photography and in-person clinical assessment by the Centers for Disease Control and Prevention (CDC) criteria after lower limb fracture surgery. Methods: Data from two large, UK-based multicentre randomized controlled major trauma trials investigating SSI and wound healing after surgical repair of open lower limb fractures that could not be primarily closed (UK WOLLF), and surgical incisions for fractures that were primarily closed (UK WHiST), were examined. Trial interventions were standard wound care management and negative pressure wound therapy after initial surgical debridement. Wound outcomes were collected from 30 days to six weeks. We compared the level of agreement between wound photography and clinical assessment of CDC-defined SSI. We are also assessed the level of agreement between blinded independent assessors of the photographs. Results: Rates of CDC-defined deep SSI were 7.6% (35/460) after open fracture and 6.3% (95/1519) after closed incisional repair. Photographs were obtained for 77% and 73% of WOLLF and WHiST cohorts respectively (all participants n = 1, 478). Agreement between photographic-SSI and CDC-SSI was fair for open fracture wounds (83%; k = 0.27 (95% confidence interval (CI) 0.14 to 0.42)) and for closed incisional wounds (88%; k = 0.29 (95% CI 0.20 to 0.37)) although the rate of photographically detected deep SSIs was twice as high as CDC-SSI (12% vs 6%). Agreement between different assessors for photographic-SSI (WOLLF 88%, k = 0.63 (95% CI 0.52 to 0.72); WHiST 89%; k = 0.61 (95% CI 0.54 to 0.69)); and wound healing was good (WOLLF 90%; k = 0.80 (95% CI 0.73 to 0.86); WHiST 87%; k = 0.57 (95% CI 0.50 to 0.64)). Conclusion: Although wound photography was feasible within the research context and inter-rater assessor agreement substantial, digital photographs used in isolation overestimated deep SSI rates, when compared to CDC criteria. Wound photography should not replace clinical assessment in pragmatic trials but may be useful for screening purposes where surgical infection outcomes are paramount. Cite this article: Bone Joint J 2021;103-B(12):1802–1808.